2002
DOI: 10.1108/09556220210424198
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and compressional characteristics of air‐jet textured yarn woven fabrics

Abstract: The effect of pick density, constituent filament fineness and heat‐setting on the fabric thickness and compressional properties have been studied before and after laundering. With the increase in pick density fabric thickness, compression and compressibility increases up to a certain extent. Coarser filament textured yarn fabric have higher thickness, compression and compressibility than that of finer filament textured yarn fabrics. Heat‐set fabrics possess higher thickness, compression and compressibility tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…Mukhopadhyay et.al. analysed fabric extension and recovery properties of woven fabrics developed using air-jet textured yarn to obtain proper stretch properties [25]. Dunja and Vili studied stretching behavior of woven fabric with elastane and they found that the elastane yarn affects viscoelastic properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Mukhopadhyay et.al. analysed fabric extension and recovery properties of woven fabrics developed using air-jet textured yarn to obtain proper stretch properties [25]. Dunja and Vili studied stretching behavior of woven fabric with elastane and they found that the elastane yarn affects viscoelastic properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…; Mukhopadyhay et al . ). A description of warm‐cool feel is a common basic subjective description of fabric hand and sometimes, quality (Bishop ).…”
Section: Fabric Properties Affecting Sensorial Comfortmentioning
confidence: 97%
“…This stems from the fineness of the individual component filaments (Mukhopadyhay et al . ; Behery ). Yarn production methods do affect the tactile behavior of yarns.…”
Section: Influence Of Fibers and Yarns On Sensorial Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…Chathura ve Bok [8] pamuklu elastanlı ribana örme kumaşın onuncu yıkamadan sonra daha dengeli olduğunu, pamuk ribana kumaşın ise yıkama sayısı artsa dahi aynı dengeli duruma gelmediğini, elastanlı ve elastansız ribana örme kumaş-ların en çekme, boy çekme ve may dönmesi gibi parametreler üzerine sıklık faktörü ve relaksasyonun etkisinin değiştiğini ve bunun için de iki veya üç yıkamadan sonrasının herhangi bir etkisinin olmadığını ortaya koymuşlardır. Mukhopadhay ve arkadaşları [9] pamuk/spandex örme kumaşların uzama ve geri dönme özellikleri üzerine yaptıkları çalışmada uzama ve geri dönmenin ilk yıkamada önemli olup sonrasında önemsiz olduğunu, yıkamanın elastik özellikleri azalttığını ifade etmişlerdir. Senthilkumar ve Anbumani [2] elastanlı ve elastansız düz örgü kumaşların dinamik elastik davranışları üzerine yıkamanın etkisini analiz ettikleri çalışmada dinamik geri dönmenin elastanlı kumaşta elastansız kumaşa göre boy yönünde %40 daha fazla, en yönünde %24 daha fazla olduğunu, yıkamanın her iki kumaşta da dinamik geri dönme ve gerilimi en ve boy yönünde etkilemediğini ifade etmişlerdir.…”
Section: Introductionunclassified